Homogenized model of diffusion in a locally periodic porous medium with nonlinear absorption at the boundary - Goncharenko, M. V.; Khilkova, L. A. (Reports of the National Academy of Sciences of Ukraine, 2016)
We consider a boundary-value problem describing the process of stationary diffusion in a locally periodic porous medium with nonlinear absorption on the boundary. We study the asymptotic behavior of the solution, when the scale of the microstructure of the medium ε → 0. We have constructed the homogenized equation describing the main term of the asymptotics and deduced explicit formulas for effective characteristics of a medium that are coefficients of this equation.